Effective Word Reading Instruction: What Does the Evidence Tell Us?. (November 2017) - Henbest, Victoria S.; Apel, Kenn
This article is a report of recent evidence on methods for teaching young and struggling readers to read words. Specifically, evidence comparing synthetic and analytic phonics instruction was reviewed as well as the benefit of instruction in encoding and morphological awareness. The evidence reviewed suggests that instruction in synthetic and analytic phonics are both effective methods for teaching word reading to young and struggling readers and the inclusion of encoding in early reading instruction may provide added benefit. Furthermore, several investigations have found instruction in morphological awareness to be beneficial for improving young students' word reading. More research is needed to investigate the effectiveness of incorporating encoding and morphological awareness instruction into early reading programs.